Implementation of E-government in Education Services through the Development of Education Management Information Systems (SIMDIK) in Malang City - Dini Kusuma Arya Wardana; Muhammad Kamil; Yana Syafriana Hijri (Universitas Teuku Umar, 2022)
Electronic Government (E-government) application in various regional apparatus organizations is the government's effort to provide excellent public services to the community. The implementation of e-government through the development of an Education Management Information System is a policy taken by the Malang City Government to solve educational management problems and provide optimal educational services. This research is qualitative research with a case study approach. The research location is in the Department of Education and Culture of Malang City and the Department of Communication and Information Technology of Malang City. The findings of researchers in the field indicate uncertainty in the implementation of e-government through the development of an education management information system (SIMDIK) in Malang City. The massive commitment of the institution is inversely proportional to the support of the state civil apparatus. It impacts uncertainty in the implementation of e-government through the development of education management information systems in the city of Malang. This inconsistency is motivated by inadequate resources. In the end, the implementation of e-government through the development of education management information systems in Malang City failed. The existence of these failures impacts the non-fulfilment of the dimensions of smart governance, which at the same time hinders the realization of good governance.